ENDOCRINE DISORDERS IN DOGS: EPIDEMIOLOGY, CLINICAL PRESENTATION, AND DIAGNOSTIC METHODS - Daniela Neagu; Vlad-Emil Luca; Răzvan Codea; Cristian Popovici; Anca Bărbos; Ștefania Dandea; Dragoș Hodor; Alexandra Biriș (Agricultura)
This study evaluates the clinical, epidemiological, and diagnostic aspects of major endocrine disorders in dogs. The research focused on common endocrine disorders, breed predisposition, sex, neutering status, age, weight, symptom prevalence, and comorbidities. 46 canine patients meet the criteria and were included in the study. Diabetes mellitus (55%) and hyperadrenocorticism (22%) were the most common, with seasonal trends noted for diabetes in spring and hyperadrenocorticism in winter. Middle-aged or geriatric dogs showed higher incidences, and overweight dogs frequently had Cushing's syndrome. Small breeds like West Highland White Terriers (24%) and Bichons (16%) were commonly diabetic, while hyperadrenocorticism was seen in Bichons (30%), Dachshunds, and Poodles (20%). Comorbidities included pancreatitis (10.86%), hepatomegaly (10.86%), and biliary mucocele (15.21%). Diagnostic methods included glucose monitoring, glycemic curve analysis, and low-dose dexamethasone suppression tests, with imaging (ultrasound) confirming endocrine gland involvement in 50% of Cushing's cases. Major risk factors were breed, age, and neutering status, with higher incidences in geriatric (≥10 years) and intact small breed dogs, but no significant sex predisposition. Digestive symptoms and general health deterioration were common clinical signs, requiring biochemical and hematological evaluations for definitive diagnosis in 41% of cases.